TINJAUAN YURIDIS TERHADAP PELAKU TINDAK PIDANA KERUSAKAN BIOTA DAN EKOSISTEM LAUT DI WILAYAH PAPUA BARAT DAYA - Mitra Blessing Rotikan (Jurnal Riset Multidisiplin Edukasi, 2026)
Indonesia, as an archipelagic country, has enormous marine biodiversity and ecosystems, especially in the Southwest Papua region. However, these resources face serious threats from activities that destroy the marine environment, especially destructive fishing practices such as the use of explosives and fish poisons (potassium/cyanide). These criminal acts have a direct impact on coral reef destruction, declining fish stocks, and disruption of the marine ecosystem balance. This study aims to analyze law enforcement against perpetrators of crimes against marine biota and ecosystems in the Southwest Papua region and to identify the obstacles faced by law enforcement officials in resolving these cases. The research method used is normative juridical with a statute approach and a case approach. Data was obtained through a literature study of legislation, legal literature, and court decisions related to fisheries crimes. The results of the study show that, normatively, the legal instruments governing the protection of marine biota and ecosystems are adequate. However, in practice, law enforcement has not been optimal. The main obstacles include limited marine surveillance facilities and infrastructure, the vastness of the waters, low legal awareness among coastal communities, and weak coordination between agencies. Therefore, it is necessary to strengthen integrated law enforcement, increase the role of law enforcement officials, and take a preventive and educational approach to coastal communities in order to preserve marine biota and ecosystems in Southwest Papua.